The influence of Tawhidic paradigm in sustaining the training of soul preachers (Murabbi) for harmonious society (Ummah) - Mhd. Sarif, Suhaimi (2014)
This study explores the influence of Tawhidic paradigm in sustaining the training program for producing Murabbi of the Ummah. In Islamic terms, Murabbi plays the roles of teachers, preachers, shapers and moulders of their students to execute the fundamental roles as servants and vicegerents of Allah. The traditional methods of training through small study circle (halaqah), group seminar (ijtima’ am), practicum (tamrin), annual boot camp (mukhayyam), and so forth need an adjustment to align with the contemporary situations. The contents and the delivery methods of training also require contemporary social and globalization need. The Tawhidic paradigm remains as the fundamental belief system despite the adjustment in the methods of training and the contemporary curriculum to train individuals to be murabbi for the ummah. This study interviewed selected academicians who had undergone Islamic preaching training as Murabbi from secondary school era at home country until postgraduate studies in overseas. The results showed that there are changes and modifications in the training module for murabbi to reflect different situations and level of commitments that the murabbi faced at different stages of life. The study could be improved in terms of contents validity and reliability with it involves more informants and the use of quantitative instruments.